Tungarar Jehovald, Yarildewallin : extracts from the Holy Scriptures in the language of the tribes inhabiting the lakes and lower Murray, and called Narrinyeri. - Taplin, George; Taplin, George; British and Foreign Bible Society. South Australian Auxiliary ([Adelaide, South Australia] : South Australian Auxiliary of the British and Foreign Bible Society, 1926)
Selection taken from Genesis, Exodus, St. Matthew, St. John, & possibly the Lords Prayer; reprinted from 1864 edition.
"From the translation of Mr. George Taplin, missionary agent of the Aborigines' Friends' Association at Point MacLeay"
From the translation of George Taplin.
Reprinted 1926.
Also available online
Text in Ngarrindjeri and Yaraldi.
Keywords: Ngarrindjeri language S69.; Ngarrindjeri / Narrinjeri people (S69) (SA SI54-13); Yaraldi language S8.; Yaraldi / Yaralde people (S8) (SA SI54-13); Language - Texts and translations - non-Aboriginal to Aboriginal language; River Murray (SW NSW, N Vic, SE SA SI54, SI55); South East South Australia (SE SA SI54, SJ54); Australian